GAMBARAN GAMOPHOBIA PADA WANITA YANG MEMILIKI RIWAYAT KDRT (KEKERASAN DALAM RUMAH TANGGA) - Ravasha Marits; Eko Hardi Ansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the phenomenon of gamophobia among early adult women with a history of domestic violence. Applying a qualitative approach throygh design of case study, the study used two female participants aged 20–30 years who were unmarried and had overcome domestic violence within their family. Data were taken by using kind of in-depth semi-structured interviews done in three sessions for each participant and analyzed by applying the interactive Miles, Huberman, and Saldaña model, complemented by thematic coding. The findings reveal that gamophobia does not emerge as an isolated condition, but is shaped by early relational experiences within the family, particularly those characterized by emotional distance, verbal abuse, and psychological insecurity. Both participants demonstrated anxiety responses, emotional regulation difficulties, and negative perceptions of marriage as a potentially harmful and unsafe institution. Furthermore, participants exhibited avoidant tendencies in romantic relationships, including emotional distancing and reluctance to engage in long-term commitment. These patterns are closely related to observational learning processes from parental relationships and unmet psychological needs for relatedness. Despite these negative perceptions, the findings also indicate an ambivalent stance toward marriage, where participants still acknowledge the possibility of marriage under conditions of trust, emotional readiness, and a supportive partner. This study highlights the complex interplay between traumatic family experiences, psychological responses, and the construction of meaning toward marriage. The results underscore the importance of trauma-informed psychological interventions to support individuals with similar backgrounds in developing healthier relational perspectives